Mouth Rehabilitation in Children with Atrial Septal Defect and Epilepsy Under General Anesthesia: A Case Report - Tifanny Yuliarti Pelawi; Meirina Gartika; Machmud Al-Husyaery (International Journal Labs, 2026)
Children with congenital heart disease and epilepsy require special consideration in pediatric dental treatment because systemic conditions, medication use, and the risk of medical emergencies may complicate oral rehabilitation procedures. Atrial septal defect (ASD) is associated with concerns regarding infective endocarditis and perioperative management, while epilepsy may increase the risk of seizures during stressful dental procedures. This study aimed to describe the management of comprehensive oral cavity rehabilitation in a child with ASD and epilepsy under general anesthesia and to discuss its relevance to pediatric dental practice. This research used a case report approach involving a 10-year-old girl with multiple carious teeth, ASD, and epilepsy. Preoperative evaluation was conducted through consultation with a pediatrician and anaesthesiologist, supported by thoracic radiography, panoramic radiography, and hematological examination. Dental procedures, including restorations, pulpotomy, extraction, and fluoride varnish application, were completed in a single session under general anesthesia using sevoflurane inhalation induction. The results demonstrated that comprehensive oral rehabilitation under general anesthesia was successfully performed without intraoperative or postoperative complications. Multidisciplinary coordination, individualized treatment planning, infection control, and strict perioperative monitoring contributed to treatment success. In conclusion, oral rehabilitation under general anesthesia can be a safe and effective treatment option for pediatric patients with ASD and epilepsy when supported by careful preoperative assessment and multidisciplinary management.